Isolation and Identification of Stigmasterol in vivo and in vitro from Sesamum indicum - Sharma, Priyanka; Sarin, Renu (Asian Journal of Biological and Life Sciences, 2012)
In the present investigation, isolation and identification of stigmasterol has been carried out in vivo and in vitro from Sesamum indicum L. of pedaliaceae family. Quantification data revealed that the total sterol content was higher in callus than leaves. The in vitro studies showed that the maximum amount of total sterol was found in 6 weeks old tissue and minimum in 2 weeks old callus culture. In vivo studies showed higher content of sterol was in leaf and lower was in stem. The present investigation was aimed to investigate stigma sterol present in P. murex. Stigma sterol has been isolated from various plant parts and callus cultures of S. indicum and comparable to that of the standard stigmasterol .